PENERAPAN PENDEKATAN KETERAMPILAN PROSES SAINS UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V-B SDN 045 TARAKAN - Samsuri Alamsyah; Muhsinah Annisa; Dedi Kusnadi (Faculty of Teaching and Education, University of Wiraraja, 2018)
The purpose of this research is to improve science learning outcomes by applying science process skill approach to students of grade V-B SDN 045 Tarakan. The type of research used is Classroom Action Research (PTK). The subjects were 31 students, male students were 16 students and 15 students. This study was conducted in two cycles each cycle consisting of planning, action, observation, and reflection. Data obtained in this study include observation sheet of teacher activity, student activity, cognitive and psychomotor research. The results of research by applying science process skill approach can improve science learning outcomes in students of grade V-B SDN 045 Tarakan. In cycle I completeness of learning result of cognitive aspect 54,839% to 90,322% in cycle II, psychomotor aspect of cycle I is 64,516% to 100% in cycle. So it can be concluded that the research has been successful and in accordance with success indicators.